2021
DOI: 10.1002/cpe.6533
|View full text |Cite
|
Sign up to set email alerts
|

A new method for image classification and image retrieval using convolutional neural networks

Abstract: This article proposes a new method for image classification and image retrieval. The advantages of the proposed method are its high performance and requiring less memory compared to other methods. In order to extract image features, a Convolutional Neural Network (CNN), AlexNet, has been used. For image classification, we design a committee of four classifiers trained on graphics cards, narrowing the gap to human performance. For image retrieval, the similarity between extracted features from dataset images an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In 2022, in the investigation of Giveki et al they found another strategy for picture order and picture recovery utilizing convolutional brain networks [21]. Contrasted and different strategies, this technique enjoys the benefits of superior execution and less memory.…”
Section: Application Of Cnn In Other Field and Time-space Cnnmentioning
confidence: 99%
“…In 2022, in the investigation of Giveki et al they found another strategy for picture order and picture recovery utilizing convolutional brain networks [21]. Contrasted and different strategies, this technique enjoys the benefits of superior execution and less memory.…”
Section: Application Of Cnn In Other Field and Time-space Cnnmentioning
confidence: 99%
“…(2022). [5] This study comes up with new ways to sort and find images. The suggested way works quickly and doesn't use much memory.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments show that the suggested method works better than the current situation. [5] Al-Jubouri, H. A., & Mahmmod, S. M. [6] A lot of the work that CBIR does for picture recognition depends on feature descriptions to bridge the language gap and pull out visual characteristics. We used known precision measures to compare different methods to ones that had been tried before.…”
Section: Related Workmentioning
confidence: 99%
“…The massive amount of data available on the internet has attracted many researchers to work on various fields such as computer vision (Giveki et al 2017 ; Montazer et al 2017 ), transfer learning (Giveki et al 2022 ), data science (Mosaddegh et al 2021 ; Soltanshahi et al 2022 ), social networks (Ahmadi et al 2020 ), knowledge graph (Molaei et al 2020 ). Knowledge graphs have many applications in fields such as health (Li et al 2020 ), finance (Huakui et al 2020 ), education (Shi et al 2020 ), cyberspace security (Zhang and Liu 2020 ), social networks (Zou 2020 ).…”
Section: Introductionmentioning
confidence: 99%